The effect of feeding gliricidia on reproductive and productive performances of Javanese Fat-tailed sheep - Supriyati .; I.G.M Budiarsana; Yosep Saefudin; I. Ketut Sutama (Indonesian Center for Animal Research and Development (ICARD), 1995)
The effect of feeding gliricidia on reproductive and productive performances of Javanese Fat-tailed (JFT) sheep was studied.Thirty-two 1FT ewe lambs (ahmtt 4-5 months of age and liveweight of 12-14 kg) were randomly divided into four treatment groups . They were given free access of King grass (Pennisetttnt putrtoreophoides) dan gliricidia (Gliricidia sepiwn, Jaeq) leaf with ratio 100:0% (Group A= control), 75 :25% (Group B), 50 :50% (Group C), and 0:100% (Group D) . All groups were suplemented with concentrate (GT03, Indofeed) at 1008/head/day. Forages were given 2 .5-3% (dry-matter) of liveweight . Results showed that feeding gliricidia 25-100% of the total forages increased dry matter intake by 5.3-19 .9% and crude protein 39 .3-142 .1 % . But NDF consumption decreased 36 .9-8 .4%. Higher nutrient intake was reflected into an increase in growth-rate which associated with an increase inovulation rate (16.7-116 .7%) and pregnancy rate.